Plasmon-mediated photopolymerization maps plasmon fields for silver nanoparticles - Stamplecoskie, Kevin G. (2011)
Visible light exposure of films containing silver nanoparticles (AgNPs) shows that the enhanced field around AgNPs in a thin film containing an azo free radical initiator (AIBN) and a triacrylate selectively cross-links the triacrylate within the plasmonic region around the particles. The cross-linked polymer is less soluble than its precursor and behaves as a solubility switch. After the film is developed with ethanol, polymer-encapsulated nanoparticles are preserved on the surface. The 8-10 nm polymer structure that encapsulates the particles effectively maps and preserves the morphology of the plasmon field in AgNP-controlled nanostructures. © 2011 American Chemical Society.